Pendampingan Pembuatan Nomor Induk Berusaha, Sebagai Bentuk Implementasi dalam Pengembangan UMKM di Desa Tebing Kaning, Kecamatan Arma Jaya, Kabupaten Bengkulu Utara - Biomed, Marisadonna Asteria M.; Afsyah, Aulia Nurul; Wardi, Ahmad Suhro; Arsih, Chairunnisa Della; Simbolon, Cinthya Claudia; Hutasoit, Marta Kristina; Gutama, Mebryando; Santaria, Santaria; Igamario, Sultan Syarief; Kesuma, Erwin; Ramdani, Syahrul Oktarian; Simanullang, Yulia Oktaviani; Meiriska, Dwita; Ramadanil, Nofri; Toar, Andro Yesaya; Pujiana, Ajeng (Civiliza Publishing, 2024)
This community service program aims to improve the legality of micro, small, and medium enterprises (MSMEs) in Tebing Kaning Village through assistance in registering a Business Identification Number (NIB). This activity is carried out by providing counseling on the importance of NIB, conducting field observations, and providing direct assistance to MSME actors in the registration process through the Online Single Submission (OSS). The results of this program show a significant increase in awareness and understanding of MSME actors about the importance of NIB. In addition, a number of MSMEs have succeeded in obtaining NIB, thereby increasing the legality of their businesses and opening up opportunities for access to various government programs. This program shows that intensive assistance can be an effective solution in overcoming the obstacles faced by MSMEs in managing permits.